Pendekatan Heutagogi Untuk Mewujudkan Merdeka Belajar Pada Blended Learning Media Pembelajaran PAI di IAI Hasanuddin Pare - Nuhdi Futuhal Arifin (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2023)
There is always a revolution in learning to keep up with the times. The concept of education based on IOT (Internet Of Thing) opens the widest possible gate of learning independence for generation Z. The heutagogical approach using the Self-Determined Learning Model of Instruction (SDLMI) provides 3 phases in the form of setting a goal, taking action and adjusting goals or plans . The research was carried out with a qualitative approach using a simple random sampling technique. The results of the study, namely: (1) By setting a goal, students are able to know and measure their initial abilities and determine habits that must be changed so that they can add insight (2) In Take Action students are able to identify obstacles that hinder achieving goals and determine steps solutions that are carried out as a solution to the problem of the obstacles encountered. (3) By adjusting goals or plans, students are able to evaluate the determination of goals and actions that have been done in the form of optimizing the use of information technology and maximizing collaboration is observed to support the development of students' cognitive and metacognitive skills. (4) Students are able to question, consider and evaluate things needed during learning to improve abilities so that the steps taken become a self-reflection for students and become an experience of a learning process with a deeper understanding.